Ecology of Scaphium macropodum in the Sarolangun Jambi Production Forest Area - Lubis, Rizky Febriana Br; Marpaung, Sutan Sahala Muda; Srena, Mona Fhitri; Kusuma, Yosie Syadza; Batubara, Junianto S.; Siadari, Ulidesi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Pengulu Tribe in Limun District, Sarolangun Regency, Jambi Province, has long used the fruit of *Scaphium macropodum*—locally known as